The Effect of Ratio of Pandanus Juice with Ginger Juice and the Ratio of Sugar with Blend of Juices on Quality of Syrup of Pandanus - Atania Br Tarigan; Terip Karo-Karo; Ismed Suhaidi (Universitas Sumatera Utara, 2016)
This research was aimed to know the effect of ratio of pandanus juice with gigger juice and the ratio of sugar mass with blend of juices on pandanus syrup quality. This research was conducted using a factorial completely randomized design with two factors, i.e the ratio of pandanus juice and gingger juice (S) : (55% : 45%, 60% : 40%, 65% : 35%, 70% : 30%) and the mass of sugar with blend of juices (G) (11:20, 12:20, 13:20, 14:20). The parameters were vitamin C content, total soluble solid, pH value, viscosity, soluble capacity, total microbe, total sugar, score test of color, flavor, taste, and hedonic test of color, flavor and taste. The results showed that the ratio of pandanus juice and ginger juice had a highly significant effect (P<0,01) on vitamin C content, pH value, viscosity, soluble capacity, total microbe, score test of taste and hedonic test of color, flavor, and taste but had no significant effect (P>0,05) on total soluble solid, total sugar, score test of color, and score test of flavor. The mass of sugar with blend of juices showed a highly significant effect (P<0,01) on vitamin C content, pH value, total soluble solid, viscosity, total sugar, and soluble capacity, but had no significant effect (P>0,05) on score test of flavor, score test of color, score test of taste, and hedonic test of, color, flavor and taste. Interaction between the two factors showed a highly significant effect (P<0,01) on vitamin C content, pH value, and total sugar but had no significant effect (P>0,05) on total soluble solid, viscosity, soluble capacity, total microbe, score test of color, score test of flavor, score test of taste, and hedonic test of, color, flavor and taste. . The ratio of 55% pandanus juice and 45% ginger juice and the ratio of sugar mass with blend of juices of 14:20 had the best quality of pandanus syrup. Keywords : ginger, ginger juice, pandanus, pandanus juice, sugar, syrup.